FINANCIALISATON OF SAVINGS: THE SUBTLE POWER OF NUDGES IN SHAPING PERSONAL FINANCE - Kaur, Amanjot; Gupta, Monica (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Indian financial services landscape has evolved and transformed in the last decade . The use of technology and policy push has catalysed the evolution. In the evolving landscape of personal finance, the shift from traditional saving methods to financialized saving strategies represents a significant behavioural and economic transition . This paper examines how the application of nudge theory has been instrumental in steering this transformation. As individuals increasingly move from conventional savings like bank deposits to more complex financial vehicles such as stocks, mutual funds, and retirement accounts, understanding the role of behavioural nudges in this shift becomes crucial. The study explores the application of nudge theory as proposed by Thaler and Sunstein(2008), exploring its practical implementation in personal finance. The study explores the awareness level of college students for financial inclusion schemes.. Employing a qualitative approach also compiles the inputs of experts and stakeholders to understand the impact of these nudges on personal saving habits. The papers explores how subtle modifications in choice architecture and policy design, such as automatic enrolment in pension plans, default fund options in investment schemes, and simplification of financial choices, effectively nudge individuals. It conclusively underline the need for Nudging for broadening the investor base with the balance of informed decision making to safeguard financial stability and financial wellbeing.